Compatibility tests between molten Aluminium alloys and recycled ceramics from inorganic industrial wastes. (December 2017) - Xu, Haoxin; Sadiki, Najim; Magro, Fabio Dal; Py, Xavier; Mancaux, Jean-Marie; Romagnoli, Alessandro
Abstract: Recycled ceramics from industrial wastes, compared with traditional high-purity ceramics, present high market potential as refractory materials due to their low cost production process with very friendly environmental impacts. In order to study the feasibility of using recycled ceramics as the encapsulation material in the application of high temperature Latent Heat Thermal Energy Storage system, this paper investigates the compatibility of recycled ceramics with three kinds of aluminium-silicon alloys at high temperature. The recycled ceramics explored are Cofalit from asbestos containing waste and steel slags. The study consists of a steady state thermal treatment of both ceramics in contact with the three different alloys at 1000°C for 100 hours, and a post instrumental characterization of ceramic samples by Environmental Scanning Electron Microscopy and Energy Dispersive Spectrometry, to understand the chemical and structural transformation of each ceramics. Results show that Cofalit has chemical interactions with aluminium alloys, while steel slag presents an excellent corrosion resistance to molten aluminium alloys and is further recommended as an encapsulation material for molten aluminium alloys at high temperature.